Imperial dialectics and epistemic mapping: From decolonisation to anti-Eurocentric IR. (June 2020) - Murray, Christopher
What would it mean to construct a post-imperial discipline rather than a 'post-Western' one? 'Post-imperial' means addressing the ways in which colonial empires divided the world into separate realms of human capability and thought. The binary categories of Western and Eastern, or Western and non-Western, represent one such way of dividing the world according to an imperial imaginary. Rather than merely excluding, these divisions created justifications for local universalisms and power structures. Yet, many anti-Eurocentric scholars now make use of these categories in order to argue for fixed epistemic differences between Western and non-Western populations. Accordingly, I critique the imperial division of the world by drawing on the intellectual trajectories of two thinkers who struggled against empire in the 20th century: WEB Du Bois and Frantz Fanon. Du Bois and Fanon were both aware of how ethnic and cultural foundations for politics could reproduce imperial order, and, therefore, offer potential alternatives to Western/non-Western ontologies. This includes recognising that representations of difference are processual, determined by strategic necessity, and subject to incentives to represent difference within hierarchical institutions. This article builds on recent studies in International Relations and other disciplines to think through the legacies of empire in knowledge production, and to push towards more historical and relational approaches to world political and social inquiry.